Reprogramming‐derived gene cocktail increases cardiomyocyte proliferation for heart regeneration - Yuan‐Yuan Cheng; Yu‐Ting Yan; David J Lundy; Annie HA Lo; Yu‐Ping Wang; Shu‐Chian Ruan; Po‐Ju Lin; Patrick CH Hsieh (EMBO Molecular Medicine)
Abstract Although remnant cardiomyocytes (CMs) possess a certain degree of proliferative ability, efficiency is too low for cardiac regeneration after injury. In this study, we identified a distinct stage within the initiation phase of CM reprogramming before the MET process, and microarray analysis revealed the strong up‐regulation of several mitosis‐related genes at this stage of reprogramming. Several candidate genes were selected and tested for their ability to induce CM proliferation. Delivering a cocktail of three genes, FoxM1, Id1, and Jnk3‐shRNA (FIJs), induced CMs to re‐enter the cell cycle and complete mitosis and cytokinesis in vitro. More importantly, this gene cocktail increased CM proliferation in vivo and significantly improved cardiac function and reduced fibrosis after myocardial infarction. Collectively, our findings present a cocktail FIJs that may be useful in cardiac regeneration and also provide a practical strategy for probing reprogramming assays for regeneration of other tissues.